Resolution of low-velocity control in golf putting differentiates professionals from amateurs - Hasegawa, Y.; Fujii, K.; Miura, A.; Yamamoto, Y. (Journal of Sports Sciences, 2017)
It is difficult for humans to apply small amounts of force precisely during motor control. However, experts who have undergone extended training are thought to be able to control low-velocity movement with precision. We investigated the resolution of motor control in golf putting. A total of 10 professional and 10 high-level amateur golfers participated. Putting distances were 0.6-3.3 m, in increments of 0.3 m. We measured the impact velocity and the club-face angle at impact, and the acceleration profile of the downswing. The professionals showed significantly smaller coefficients of variation with respect to impact velocity and smaller root mean square errors in relation to acceleration profiles than did the amateurs. To examine the resolution of motor control for impact velocity, we investigated intra-participant differences in the impact velocity of the club head at two adjacent distances. We found that professionals had higher velocity precision when putting small distance intervals than did amateurs. That is, professionals had higher resolution of low-velocity control than did high-level amateurs. Our results suggest that outstanding performance at a task involves the ability to recognise small distinctions and to produce appropriate movements.